Magnetic Resonance Imaging and Magnetic Resonance Arthrography Are Both Reliable and Similar When Measuring Hip Capsule Thickness in Patients With Femoroacetabular Impingement Syndrome - Devin L. Froerer, B.S; Ameen Z. Khalil, M.S; Allan K. Metz, M.D; Reece M. Rosenthal, B.S; Joseph Featherall, M.D; Travis G. Maak, M.D; Stephen K. Aoki, M.D (Elsevier, 2024)
Purpose: To propose an accurate method of measuring hip capsular thickness in patients with femoroacetabular impingement syndrome and to compare the reliability of these measurements between magnetic resonance imaging (MRI) and magnetic resonance arthrography (MRA). Methods: A previously established database of patients with femoroacetabular impingement syndrome (FAIS) was used to identify candidates with preoperative MRI or MRA from November 2018 to June 2021. Two reviewers independently examined preoperative imaging for 85 patients. Capsular thickness was measured in 12 standardized locations. Intraclass correlation coefficients (ICCs) were calculated using an absolute-agreement, 2-way random-effects model. Using the same method, 30 patients were randomly selected for repeat measurements by 1 reviewer following a washout period. Ten additional patients with preoperative MRI and MRA of the same hip were identified to compare measurements between modalities using paired samples t test. Results: ICCs for measurements on MRIs and MRAs using these proposed measurements to compare inter-rater reliability were 0.981 and 0.985. ICCs calculated using measurements by a single reviewer following a washout period for intrarater reliability were 0.998 and 0.991. When comparing MRI and MRA measurements in the same patient, t test for all pooled measurements found no difference between modality (P = .283), and breakdown of measurements by quadrant found no difference in measurements (P > .05), with the exception of the inferior aspect of the capsule on coronal sequences (P = .023). Conclusions: In patients with FAIS, both MRI and MRA have excellent reliability for quantifying hip capsular thickness. A difference in capsular thickness was found only when comparing MRI and MRA on inferior coronal aspects of the hip capsule, indicating interchangeability of these imaging modalities when measuring the clinically important aspects of the hip capsule. Level of Evidence: Level IV, diagnostic case series.